Impact of a dual task intervention on physical performance of older adults who practice physical exercise - Larissa Borges Medeiros; Juliana Hotta Ansai; Marcele Stephanie de Souza Buto; Verena de Vassimon Barroso; Ana Claudia Silva Farche; Paulo Giusti Rossi; Larissa Pires de Andrade; Anielle Cristhine de Medeiros Takahashi (Universidade Federal de Santa Catarina, 2018)
Physical exercises, especially multicomponent training, can improve cognitive functions and physical impairments in older adults. The aim this study was to purpose of this two-arm clinical trial was to investigate the effects of the addition of a dual task to multicomponent training on physical performances of community-dwelling older adults who practice physical exercise. Seventy-one older adults were divided into a control group (CG) and intervention group (IG). Participants of the CG performed isolated multicomponent training, participants of the IG performed multicomponent training associated with cognitive tasks and both protocols lasted 12 weeks. The assessment consisted of flexibility, handgrip strength, lower limb strength, balance, functional mobility and aerobic capacity. The CG presented greater flexibility than the IG, regardless of time. There was a worse performance in lower limb strength, regardless of group. The addition of a dual task to the multicomponent training was not able to improve physical performances of older adults. Further studies are needed to confirm whether the dual task training contributes to both cognitive and physical benefits in older adults who practice physical exercise.